AN ANALYSIS OF STUDENTS TECHNIQUES IN PARAPHRASING AT UNIVERSITY PGRI PALEMBANG - Ibnu Ash Shidiqi; Evi Rosmiyati; Marleni (SMART: Journal of Multidisciplinary Educational, 2024)
ABSTRACT This study aimed to analyze students’ techniques in paraphrasing at PGRI Palembang university in the academic years of 2021/2022. There were two types of data collected in this study, namely qualitative and quantitative data. The qualitative data were used to describe the progress of the actions. The analytical method used in this study is a qualitative descriptive analysis method. The writer conducted this research in qualitative approach with deciding 16 students as the respondents by purposive sample. the data was collected by a questionnaire given to the students. after analyzing the data, the writer found that the paraphrasing technique that students used was to change the synonym technique and changing the word order and the technique is based on Beiley. The writer also found that 50% students like the material paraphrasing and those who don’t like the material because one of them doesn’t understand how to paraphrase text. The results of this study indicated that students already know how to write paraphrasing and the kind of paraphrasing techniques that students conducted and that is change the synonym technique and changing the word order.